Gender differences in the relationship between sleep and age in a Brazilian cohort: the Baependi Heart Study - Taporoski, Tâmara P.; Beijamini, Felipe; Alexandria, Shaina; Aaby, David; Schantz, Malcolm; Pereira, Alexandre C.; Knutson, Kristen L. (Journal of sleep research, 2025)
Summary Gender and age are well‐established determinants of health and sleep health that influence overall health, which also often varies by gender and age. Sleep architecture is an important component of sleep health. The goal of this analysis was to examine whether associations between age and sleep stages differ by gender in the absence of moderate–severe obstructive sleep apnea (OSA) in a rural setting in Brazil. This study conducted polysomnography recordings in the Baependi Heart Study, a cohort of Brazilian adults. Our sample included 584 women and 309 men whose apnea–hypopnea index was ≤15 events/h. We used splines to distinguish non‐linear associations between age, total sleep time, wake after sleep onset (WASO), N2, N3, and rapid‐eye‐movement sleep. The mean (standard deviation; range) age was 47 (14; 18–89) years. All sleep outcomes were associated with age. Compared to men, women had more N3 sleep and less WASO after adjusting for age. Model‐based comparisons between genders at specific ages showed statistically higher mean WASO for men at ages 60 (+13.6 min) and 70 years (+19.5 min) and less N3 for men at ages 50 (−13.2 min), 60 (−19.0 min), and 70 years (−19.5 min) but no differences at 20, 30, 40 or 80 years. The other sleep measures did not differ by gender at any age. Thus, even in the absence of moderate–severe OSA, sleep architecture was associated with age across adulthood, and there were gender differences in WASO and N3 at older ages in this rural community.